The Levellers' conception of legitimate authority - Ostrensky, Eunice (Araucaria, 2018)
This article examines the Levellers’ doctrine of legitimate authority, by showing how it emerged as a critique of theories of absolute sovereignty. For the Levellers, any arbitrary power is tyrannical, insofar as it reduces human beings to an unnatural condition. Legitimate authority is necessarily founded on the people, who creates the constitutional order and remains the locus of political power. The Levellers also contend that parliamentary representation is not the only mechanism by which the people may acquire a political being; rather the people outside Parliament are the collective agent able to transform and control institutions and policies. In this sense, the Levellers hold that a highly participative community should exert sovereignty, and that decentralized government is a means to achieve that goal.